Frontotemporal Orbitozygomatic Transcavernous Approach: Stepwise Cadaveric Dissection for a Safe Corridor - Corecha Santos, Romel; Gupta, Bhavika; Dabecco, Rocco; Santiago, Raphael Bastianon; Kaye, Brandon; Borghei-Razavi, Hamid; Adada, Badih (Journal of Neurological Surgery Part B: Skull Base, 2023)
Background Advances in skull base surgery have increased the need for a detailed understanding of skull base anatomy and its intrinsic relationship to surrounding structures. This has resulted in an improvement in patient outcomes. The frontotemporal orbitozygomatic (FTOZ) transcavernous approach (TCA) is an excellent option for treating complex lesions involving multiple compartments of the skull base, including the sellar and parasellar, third ventricle, orbit, and petroclival region.Objective This article aimed to provide a detailed cadaveric dissection accompanying a thorough procedure description, including some tips and pitfalls of this technique.Methods Microsurgical dissection was performed in four freshly injected cadaver heads at the Cranial Base Neuroanatomy Laboratory, Cleveland Clinic Florida. The FTOZ TCA was performed on both sides of the four specimens. The advantages and disadvantages were discussed based on the anatomic nuances of this approach.Results The FTOZ TCA represented a wide access to the anterior, middle, and posterior fossa. When combined with an anterior clinoidectomy, it allowed for significant and safe internal carotid artery mobilization. This approach created numerous windows, including opticocarotid, carotid-oculomotor, supratrochlear, infratrochlear, anteromedial, anterolateral, and posteromedial triangles. The only drawback was the length of the dissection and the level of surgical acumen required to perform it.Conclusion Despite its technical difficulty, the FTOZ TCA should be considered for the surgical management of basilar apex aneurysms and tumors surrounding the cavernous sinus, sellar/parasellar, retrochiasmatic, and petroclival region. Continuous training and dedicated time in the skull base laboratory can help achieve the necessary skills required to perform this approach.
Keywords: anatomic study; craniotomy; cavernous sinus; microsurgery; orbitozygomatic; skull base